ANALISIS MIKROBIOLOGI PADA JAJANAN PEDAGANG KAKI LIMA DI SEPANJANG JALAN SUTOREJO SURABAYA - Dita Artanti; Mulya Fitrah Juniawan; Ainutajriani Ainutajriani (LPPM Universitas Abdurrab, 2023)
Coliform bacteria are indicators of food contamination that can cause diseases such as diarrhea. The presence of Coliform bacteria in food or beverages indicates poor hygiene and sanitation in food service providers. The purpose of this study was to determine Coliform bacteria in street vendors' snacks along Sutorejo street in Surabaya using the MPN (Most Probable Number) method, ALT (Total Plate Number) and identification of Coliform bacteria with Biochemical tests. This research method uses laboratory experiments. The results showed, of the 12 samples of snacks, there were 4 (33%) samples that met the MPN quality requirements and 8 (67%) samples that did not meet the requirements. Based on the ALT test, 3 (25%) samples met the SNI requirements and 9 (75%) samples did not meet the requirements. Coliform bacteria identification results, there were 6 (50%) positive samples of E.coli bacteria, 2 (17%) positive samples of Klebsiella sp., 1 (8%) positive sample of Enterobacter sp. and 3 (25%) samples were not contaminated by Coliform bacteria. From the results of this study it can be concluded that there are still many snacks contaminated by Coliform bacteria and dominated by E.coli.